Services management in Asia Pacific: Issues and challenges - Jayachanran, C.; Ali, Juhary; Chatterjee, Samir; Singha, Chiamsiri (Universiti Utara Malaysia, 2007)
The book of readings, Services Management in Asia Pacific:Issues and Challenges is an outcome of the first research workshop organised by the Society for Global Business and Economic Development (SGBED) at the Asian Institute of Technology (AIT), Bangkok in January 2006.The initiative to hold the first research workshop on ‘Services Management in Asia Pacific’ grew out of the 9th International conference held in Seoul, South Korea in May 2005.In view of the importance of service business in Asia Pacific, the Curtin School of Management and the leadership of the SGBED agreed to develop a theme around service industries and implement it in Asia.The credit for successfully organising this major event goes to Dr. Singha Chiamsiri, at the School of Management, Asian Institute of Technology.Dr. Juhari Ali, Dean, Faculty of Business Management at Universiti Utara Malaysia (UUM), accepted the responsibility of publishing selected research papers in a book of readings on behalf of the SGBED in cooperation with the university publications division.The books is divided into four parts.Part one provides a conceptual understanding of services management.Part two examines service industries in China, Malaysia, India and Japan.Part three includes industry case studies that focus on low cost air carriers in South East Asia, branding and tourism in Thailand and financial derivatives market in China.